Analisis Usability Website Berbinar Insightful Indonesia Menggunakan USE Questionnaire dan Performance Test - Shaktyanti, Frenchyani Anggi; Pradini, Risqy Siwi; Kusuma, Wahyu Teja (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) STMIK Indonesia Banda Aceh, 2025)
This research analyzes the usability of the Berbinar Insightful Indonesia website using a use questionnaire and performance test to test the suitability of this website. Testing was carried out by giving 5 task scenarios and 30 questionnaires to 20 participants. Testing using task scenarios is very important for measuring the performance of a website through user experience. The research instrument used is a use questionnaire used to calculate the usability value of a website. Based on the results of the use questionnaire, the usability value was found to be 79% in the good category, apart from that, the value of the 4 aspects of the use questionnaire, namely, usefulness was equal to, ease-of-use was equal to, ease-of-learning was equal to and satisfaction was equal to. Furthermore, the results of the performance test show the participant's time to complete the task, the number of participant errors and mistakes, the participant's success rate as well as a time efficiency value of 79% and an overall relative efficiency of 98%. These findings contribute to usability testing on the Berbinar Insightful Indonesia website based on user experience.